Reproductive toxicity of fluoroquinolones in birds - Hruba, Hana; Abdelsalam, Ehdaa Eltayeb Eltigani; Anisimov, Nikolay; Bandouchova, Hana; Havelkova, Barbora; Heger, Tomas; Kanova, Miroslava; Kovacova, Veronika; Nemcova, Monika; Piacek, Vladimir; Sedlackova, Jana; Vitula, Frantisek; et al. (BMC veterinary research, 2019)
BACKGROUND: While commercial poultry and captive birds are exposed to antimicrobials through direct medication, environmental pollution may result in contamination of wild birds. Fluoroquinolones are commonly used medications to treat severe avian bacterial infections; however, their adverse effects on birds remain understudied. Here, we examine toxicity of enrofloxacin and marbofloxacin during the egg incubation period using the chicken (Gallus Gallus domesticus) as a model avian species. Laboratory tests were based on eggs injected with 1, 10 and 100 μg of fluoroquinolones per 1 g of egg weight prior to the start of incubation and monitoring of chick blood biochemistry, reproductive parameters and heart rate during incubation. RESULTS: Eggs treated with fluoroquinolones displayed reduced hatchability due to embryonic mortality, particularly on day 13 of incubation. Total hatching success showed a similar pattern, with a significantly reduced hatchability in low and high exposure groups treated with both enrofloxacin and marbofloxacin. From 15 to 67% of chicks hatching in these groups exhibited joint deformities. Hatching one-day pre-term occurred with a prevalence of 31 to 70% in all groups treated with fluoroquinolones. Embryonic heart rate, measured on days 13 and 19 of incubation, increased in all enrofloxacin-treated groups and medium and high dose groups of marbofloxacin-treated eggs. Blood biochemistry of chicks sampled at hatch from medium dose groups showed hypoproteinaemia, decreased uric acid and increased triglycerides. Chicks from the enrofloxacin-treated group displayed mild hyperglycaemia and a two-fold rise in the blood urea nitrogen to uric acid ratio. Principal components analysis based on blood biochemistry clearly separated the control bird cluster from both enrofloxacin- and marbofloxacin-treated birds. CONCLUSIONS: Fluoroquinolones induce complex adverse effects on avian embryonic development, considerably reducing the performance of incubated eggs and hatching chicks. Cardiotoxicity, which quickens embryonic heart rate, meant that the total number of heart beats required for embryogenesis was achieved earlier than in the standard incubation period, resulting in pre-term hatching. Our data suggest that enrofloxacin has a higher potential for adverse effects than marbofloxacin. To conclude, care should be taken to prevent exposure of reproducing birds and their eggs to fluoroquinolones.
Keywords: Chick Embryo; kur domácí; Animals; enrofloxacin; rozmnožování; Female; Chickens; Antibiotics; ženské pohlaví; Reproduction; Hypoproteinemia; Poultry Diseases; antiinfekční látky; Anti-Infective Agents; nemoci drůbeže; Fluoroquinolones; fluorochinolony; srdeční frekvence; Avian embryonic heart rate; hypoproteinemie; Hatchability; Pre-term hatching; zvířata; Enrofloxacin; Marbofloxacin; Heart Rate; kuřecí embryo